Comparison of Chemical and Biological Control Techniques to Stem Rot Fusarium Spp. On Fig Seedlings (Ficus Carica L.) as an Effort to Substitute Agrochemical Inputs in Environmentally Friendly Control - Pramono Hadi; Srie Juli Rachmawatie; Moh. Masnur (Postgraduate, University of Mataram, 2023)
Figs have many benefits to treat various health problems, so it is necessary to breed vegetatively so that the production of figs can increase in the future. Fig nurseries have problems with the success of seedlings caused by stem rot disease due to the attack of pathogen Fusarium spp. This study aims to determine the ability of chemical and biological control techniques in suppressing the intensity of stem rot disease caused by pathogen Fusarium spp., as well as looking for substitution of agrochemical inputs for environmentally friendly disease control. The research was conducted at greenhouse faculty of agriculture, Batik Islamic University of Surakarta, from September 15, 2020 to December 23, 2020. The study used a Complete Randomized Design (RAL), with 6 types of control technique treatments, consisting of control, biological Trichoderma spp., biological Gliocladium spp., biological Corynebacterium spp., biological PGPR, and chemical Mankozeb, which was repeated 3 times and 3 times subrepannant. Observation consists of the parameters of the incubation period of the disease, the incidence of the disease, and the severity of the disease. The results showed that the treatment of biological control techniques was able to reduce the intensity of disease attacks with the best results obtained in trichoderma spp biological control agents (APH). which is able to delay the incubation period of the disease up to 48.89hsi, reduce the incidence of the disease by 88.89%, and reduce the severity of the disease by up to 97.78% because it has antagonism abilities in the form of competition mechanisms, mycoparasites, and antibiosis. Ability APH Trichoderma spp. can be an alternative solution to substitute agrochemical inputs in disease control that is more environmentally friendly and sustainable and can maintain natural balance in agroecosystems